Voting Behaviour of Uttar Pradesh Assembly Election, 2012: A Spatial Study - Sahdev, Seema Sahdev; Hashia, Haseena (National Geographical Journal of India, 2022)
Mapping the voting behaviour and voting turn out pattern of an area is of great significance for an Electoral Geographers as it depicts the level of political consciousness and development of that area. The present paper attempts to analyse spatial pattern of voting behaviour in Uttar Pradesh in 2012 assembly elections with a view to bringing out the electoral consciousness and party performance in different Constituencies and examine voting behaviour in the context of Environmental issues. The finding of the paper reveals that there is variation in voting turnout across the region. It was highest in Rohilkhand Plains at 65 percent and lowest in the Region at 56 percent. The spatial spread of the SP's (Samajawadi Party) votes become more even with the increase in overall party vote share. The SP performed well in Awadh Plains, Ganga-Yamuna Doab and Purvanchal Region both in term of seats and votes where as the second largest party, the BSP did not formed any continuous region of high support. The national parties – the BSP and the Congress form a region of low support. In this election, young, well educated and relatively well of urban were important and influencing voting segment and voters have favoured parties on the basis of better governance and class was the main determinant of voter support.